Construction of a Complex Network Using Technological Surveillance for the Strategic Management of Science, Technology, And Research in Higher Education Institutions in Colombia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research proposes the construction of a model of technological surveillancefor the strategic management of scientific research in higher education institutions inColombia. This model is composed by an information system that includes scientificarticles, intervention plans for the regions and the nation, and information from publicpolicies related to Science, technology, and information (STI). From this data set, theconstruction of algorithms for information processing was carried out, using techniques ofautomatic text analysis and natural language processing with complex networks to detectpatterns and the configuration of trends related to science, technology, research, andinnovation, which are the guiding topics of the national science and technology system. Themain results obtained in this research are that the construction of a complex systemrevealed the topics on which scientific production is focused in the country. In addition, theanalysis of the documents related to STI referenced in in public policies analyzed for thisresearch revealed the pressing needs of different sectors and regions in the country. Finally,the research showed that the topics on which scientific research in Colombia is conductedby the educational institutions of the country does not correspond to the needs found.